From a Nineteenth-Century Classic to a Modern Graphic Novel: Batman Noël as a Multi-level Translation Practice - Saglam, Naciye (University of Bologna, 2023)
As a nineteenth-century classic, A Christmas Carol achieved instant success when published in 1843, paving the way for countless remakes of the story worldwide being produced in movie, theatre, opera, ballet, graphic novel, comic strip, parody and video game formats to this day. The graphic novel Batman Noël, published in 2011, which takes the Christmas story into the fictional city of Gotham, is one of these remakes. The work is at once an intersemiotic translation of the classic into a graphic novel while also being an adaptation of the story into the Batman universe. Lee Bermejo, the creator of Batman Noël, maintains faithfulness to the nineteenth-century classic with respect to the main idea, characters and language, but also creates a double meaning regarding the main character and transforms the message of the story by combining the verbal and the visual. In addition, Batman Noël , this time as a source text, and its translation into Turkish published under the same title (2016) reveal another fruitful area of investigation. In this interlingual and multimodal translation, while the elements such as icons, font size, and book cover are closely recreated, inconsistencies concerning so called "linguistic paratexts" (Celotti 2008) raise the question of agency. This study thus aims to explore what happened when A Christmas Carol was first transformed into the graphic novel Batman Noël and then translated from English into Turkish. The former is the process of intersemiotic translation and adaptation of the story - hence a semiotransadaptation (Chesterman 2018), whereas the latter is the process of multimodal and interlingual translation of the graphic novel. © 2023 Universita degli Studi di Bologna. All rights reserved.
Keywords: A Christmas Carol; Batman Noël; graphic novel; interlingual translation; intersemiotic translation